Studi Literatur Senyawa Metabolit Bakteri Asam Laktat Dan Kegunaannya Dalam Mengoptimalisasi Kesehatan Hewan - Tulasi, Maria Inocensia; Foeh, Nancy D.F.K; Detha, Annytha I.R (Jurnal Veteriner Nusantara, 2024)
Lactic acid bacteria are facultative anaerobic bacteria that can live in the digestive tract of animals and humans. Lactic acid bacteria have been used as a culture of fermentation, food preservatives, and food probiotics because it has antimicrobial activity and food spoilage. Antimicrobial compounds produced by lactic acid bacteria include the production of lactic acid and pH reduction, the production of acetic acid, diacetyl, hydrogen peroxide, carbon dioxide, and bacteriocin. The purpose of this literature study was to find out the metabolite compounds produced in the fermentation process of lactic acid bacteria and analyze the use of metabolite compounds produced from lactic acid bacteria. This literature study was obtained from searching and collecting some various sources using the Mendeley and Google Scholar applications. 67 libraries were obtained and after being analyzed and evaluated, there were some fermented lactic acid metabolite bacteria obtained including lactic acid, acetic acid, and propionic acid, hydrogen peroxide, carbon dioxide, diacetyl, and bacteriocin. Whereas the use of metabolite compounds produced from lactic acid bacteria can be used as metabolic compounds that are antimicrobial, immunomodulatory, and in optimizing nutrient absorption.